The Association Between Social Support and Students’ Mental Health During Academic Transitions - Elita Endah Mawarni; Mila Sari; Lisbeth Laora Silitonga; Zahra Istiqamah; Wedia Hastuti (Sustainable Applied Modification Evidence Community (SAMEC), 2025)
Although the relationship between social support and students' mental health during the academic transition is rather complicated, it always has one thing in common: social support can strengthen learning involvement and lessen the intensity of some life strains.  As a result, educational establishments must offer a structured support system through counseling, peer mentoring, and an inclusive campus community.  The purpose of this study is to offer an empirical foundation for the development of campus policies that are more sensitive to the psychosocial requirements of students, particularly in the early stages of their transition to higher education. The research subjects were 75 new students chosen by purposive sampling. The data were collected thanks to internet questionnaire submissions of a 14-day duration with Google Form platform to facilitate accessibility and get rid administrative bias. The main research instruments were two. One of them is the Social Support Scale and the Psychological Mental Health Scale. All were conducted on the social support variable's frequency distribution and descriptive statistics, and on the Distribution of Student Mental Health. The coefficients of bivariate analysis uncovered a strong direct relationship between Univariate analysis was performed on social support variables and mental health among university students. The Final Result of the Study gives confirmation that strengthening one's social support system should be closely linked to creating complete written plans for students undergoing academic transition, if we are to keep them healthy both during that period and onwards into their further studies.